The Relationship Between the Accuracy of Antihypertensive Drug Selection and the Achievement of Patients' Target Blood Pressure - Truly Anggraini; Retnowati Adiningsih (Indonesian Journal of Global Health Research, 2026)
Hypertension is an important risk factor for cardiovascular morbidity and mortality that is often found in geriatrics. Inappropriate medication use in geriatrics will have a greater negative impact. The occurrence of Drug-related problems (DPRs) in the category of appropriate antihypertensive drug selection is one of the factors that can cause failure to achieve blood pressure targets in geriatrics , due to physiological, pharmacokinetic, pharmacodynamic changes, as well as complications and polypharmacy in geriatrics. The purpose of this study was to analyze the relationship between the appropriateness of antihypertensive drug selection and the achievement of blood pressure targets in geriatric patients at the Mojogedang Community Health Center. This study was a descriptive study using an analytical cross-sectional observational design. The variables in this study consisted of the independent variable, namely the appropriateness of antihypertensive drug selection, and the dependent variable, namely the achievement of geriatric blood pressure targets. Sampling used a purposive sampling technique . The samples taken must meet the inclusion and exclusion criteria, and a total of 12 patients were eligible for sampling in this study. The results of the study showed that the results of Hypertension patients at the Mojogedang Community Health Center which were the research sample were dominated by Stage 2 Hypertension patients, namely 91.67%, while the remaining 8.33% entered Stage 1 Hypertension. The next data reported in this study was the accuracy of antihypertensive selection and the achievement of blood pressure targets. As many as 83.33% of patients who were samples in this study had received the right antihypertensive and 75% of patients were able to achieve blood pressure targets, so that statistically it can be concluded that there is a significant relationship between the accuracy of antihypertensive selection and the achievement of blood pressure targets (p value = 0.007).